Major timber trees of Guyana - Gerard, J. (Tropenbos Foundation WageningenNL, 1996)
Seeks to provide technical information to enable optimum use of the Guyanese timber species. Includes information on distribution, local names, wood description, physical and mechanical characteristics, processing characteristics, natural durability and amenability to preservative treatment etc.